2017
DOI: 10.11106/ijt.2017.10.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Transformation of Follicular Thyroid Cancer in the Lung, Liver, Bone, and Adrenal Gland

Abstract: Anaplastic transformation of differentiated thyroid cancer at distant metastatic sites is extremely rare and has a poor prognosis. It usually occurs in the thyroid gland or cervical lymph nodes. Here we report a case of anaplastic transformation arising at multiple distant metastatic sites including the lung, liver, adrenal gland, bone, and lymph nodes in a patient 3 years after total thyroidectomy for follicular thyroid cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…1 , 8 , 17 Anaplastic transformation of FC in metastatic sites was observed in 72 years old person by Lee W et al while Nakayama R et al also reported anaplastic transformation of FC in the skeletal metastatic site in 55 years old woman. 24 , 25 We also uncovered a case of FC with anaplastic transformation in 45 years old female. Unlike the above-mentioned reports, we identified the anaplastic transformation in the primary site as opposed to the metastatic site.…”
Section: Discussionmentioning
confidence: 91%
“…1 , 8 , 17 Anaplastic transformation of FC in metastatic sites was observed in 72 years old person by Lee W et al while Nakayama R et al also reported anaplastic transformation of FC in the skeletal metastatic site in 55 years old woman. 24 , 25 We also uncovered a case of FC with anaplastic transformation in 45 years old female. Unlike the above-mentioned reports, we identified the anaplastic transformation in the primary site as opposed to the metastatic site.…”
Section: Discussionmentioning
confidence: 91%
“…This period varied from a year to as long as 25 years. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] Distant metastasis can occur rarely in lung, brain, maxilla, bone and retroperitoneum. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] Sixteen out of thirty cases showed distant metastasis as depicted in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15] Distant metastasis can occur rarely in lung, brain, maxilla, bone and retroperitoneum. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] Sixteen out of thirty cases showed distant metastasis as depicted in Table 1. Solomon et al, reported a case of distant metastasis where retroperitoneal metastasis showed AT, 25 years after thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation